Influence of childhood trauma on depression in the INDDEP study. Issue 2 (3rd April 2018) - Docter, Anna Lea; Zeeck, Almut; von Wietersheim, Jörn; Weiss, Heinz
Abstract : Traumatic experiences during childhood have been shown to be associated with a higher risk for depressive disorders, more severe symptoms, higher rates of comorbidity, and poorer response to therapy. This study aims to further investigate these links in a clinical sample, focusing especially on therapeutic outcome. Data were collected in a large naturalistic study on inpatient and day hospital treatment of depression at the beginning, the end and after treatment, with this article being a secondary data analysis. Occurrence of childhood trauma, depressive and other symptoms and therapeutic results were compared using robust MANOVA, multiple regression, mixed ANOVA, and Spearman's correlation. Results provide support for a relationship between childhood trauma and depressive and general symptom severity, the age of onset of depression and the occurrence of personality disorders and somatic diagnoses. There was a significant reduction of depressive symptomatology after therapy. Patients with childhood trauma did not differ significantly from controls in their response to treatment. Clinicians should take the high probability of childhood trauma in depressive patients and the consequent risk of more severe symptoms into account when taking a history and consider adjusting treatment, even if the present data showed that patients generally benefitted from therapy.